Improving Astm A516 Grade 70 Mechanical Properties by Sandblasting Process - Zaroog, Omar Suliman; Sughanthy, S.A.P.; Isa, Mohd Rashdan; Ansari, M.N.M. (International Journal of Engineering and Technology, 2018)
Nowadays, sandblasting is commonly use in industries. The ability of sandblasting is to remove any stain, unwanted matter and many other functions making this process generally used worldwide. The effect of sandblasting on mechanical properties of ASTM A516 grade 70 was investigated in this study. Samples of the material have been sandblasted with different size of grits and times. Surface roughness, hardness and tensile was measured before and after sandblasting. The roughness test result showed that when the time duration of sandblasting increased, the roughness of the specimen also increased. Based on hardness test result, it showed that the hardness improved when the smallest size of grits was applied. However, the hardness decreased when the size of grits and time was increased. The tensile test result pattern showed quite similar to hardness test result. The size of grits and time duration for sandblasting need to set depending on application of the sandblasting process usage applied to the samples or materials.